#TITLE_ALTERNATIVE# - Hakim (NIM : 10302018), Chairil
ABSTRACT: The theory of close approach has been widely studied by astronomers since the last century. In 1976 Opik developed a theory of planetary encounters based on a sequential approach of 2 body. Extension of the Opik theory provides parameters of asteroids close approach (Milani, A and A 346, L65 L68, 1999). These parameters are Target Plane, MOID (Minimum Orbital Intersection Distance), and LOV (Line of Variations). Planetary encounter changes the orbital elements of asteroid to the new ones. Moreover, the theory of Resonant Returns is closely related to the new orbital elements, that both the Earth and asteroid will meet again at the same location as the previous encounter. If asteroid passes through the specific small regions (Keyholes) on the Target Plane it may hit the earth at its subsequent return. In this thesis the parameters of close approach for three asteroids are investigated and analyzed. The asteroids are 1999 AN10, 2000 SG344, and 99942 Apophis 2004 MN4, which belong to the class of Potentially Hazardous Asteroids, (PHAs). The software OrbFit was widely used to compute the close approach parameters for of those asteroids the next 50 years.